Correlation between Patent Foramen Ovale, Cerebral “Lesions” and Neuropsychometric Testing in Experienced Sports Divers: Does Diving Damage the Brain? - Balestra, Costantino; Germonpré, Peter (Frontiers in Psychology, 2016)
SCUBA diving exposes divers to decompression sickness (DCS). There has been considerable debate whether divers with a Patent Foramen Ovale of the heart have a higher risk of DCS because of the possible right-to-left shunt of venous decompression bubbles into the arterial circulation. Symptomatic neurological DCS has been shown to cause permanent damage to brain and spinal cord tissue; it has been suggested that divers with PFO may be at higher risk of developing subclinical brain lesions because of repeated asymptomatic embolization of decompression-induced nitrogen bubbles. These studies however suffer from several methodological flaws, including self-selection bias. We recruited 200 volunteer divers from a recreational diving population who had never suffered from DCS; we then randomly selected 50 of those for further investigation. The selected divers underwent brain Magnetic Resonance Imaging to detect asymptomatic brain lesions, contrast trans-oesophageal echocardiography for PFO, and extensive neuro-psychometric testing. Neuro-psychometry results were compared with a control group of normal subjects and a separate control group for subjects exposed to neurotoxic solvents. Forty two divers underwent all the tests and are included in this report. Grade 2 Patent Foramen Ovale was found in 16 (38%) of the divers; brain Unidentified Bright Objects (UBO's) were found in 5 (11.9%). There was no association between PFO and the presence of UBO's (P = 0.693) or their size (p = 0.5) in divers. Neuropsychometric testing in divers was significantly worse from controls in two tests, Digit Span Backwards (DSB; p < 0.05) and Symbol-Digit-Substitution (SDS; p < 0.01). Compared to subjects exposed to neurotoxic solvents, divers scored similar on DSB and SDS tests, but significantly better on the Simple Reaction Time (REA) and Hand-Eye Coordination (EYE) tests. There was no correlation between PFO, number of UBO's and any of the neuro-psychometric tests. We conclude that for uneventful recreational diving, PFO does not appear to influence the presence of UBO's. Diving by itself seems to cause some decrease of short-term memory and higher cognitive function, including visual-motor skills; this resembles some of the effects of nitrogen narcosis and we suggest that this may be a prolonged effect of diving.